Assessing the stability of the inter-industry wage structure in the face of radical economic reforms - Jorge Saba Arbache; Andrew Dickerson; Francis Green (University of Kent, Department of Economics, 2001)
We assess the stability of the wage structure in an economy experiencing substantial economic changes. We find that the structure of inter-industry wage differentials remained remarkably stable in Brazil in the face of major shocks.
Keywords: J31; 330; wage structure; inter-industry wage differentials; Brazil; Lohnstruktur; Schock; Wirtschaftsreform; Brasilien